The Palestinian press’s handling of the popular protests in the “Banat” case (قضايا سياسية, 2022)
This study deals with the mechanisms and the way newspapers (Al-Quds, Al-Ayyam and Al-Hayat Al-Jadida) handled popular protests dealt with the popular protests that resulted from the death of political dissident Nizar Banat following his arrest by the Palestinian Security forces. By using the content analysis method for the contents of these newspapers, the study found that the Palestinian daily press has paid great and significant attention to the case of Nizar Banat's death, considering that this incident revealed the crisis of democracy in the Palestinian political system. The results indicated that the majority of media coverage of the Nizar Banat case in the daily newspapers was in a negative direction, were convicted and described as an assassination, indicated that those responsible for it must be held accountable. The study recommended the need to expedite the government's response to such crises in order to ensure a more transparency and neutral in press. The study also recommended the need for the Palestinian political system to respect democratic values, human rights, release freedoms, implement laws, and move forward with political reform programmes.